2016
DOI: 10.1155/2016/9510156
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Wetting-Resistant Multiscale Nano-/Microstructured Surfaces for Viscoelastic Liquid Repellence

Abstract: We demonstrate exceptional wetting-resistant surfaces capable of repelling low surface tension, non-Newtonian, and highly viscoelastic liquids. Theoretical analysis and experimental result confirm that a higher level of multiscale roughness topography composed of at least three structural length scales, ranging from nanometer to supermicron sizes, is crucial for the reduction of liquid-solid adhesion hysteresis. With Cassie-Baxter nonwetting state satisfied at all roughness length scales, the surface has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Furthermore, surface roughness in multiple length scale has been proven as the key to achieve more stable Cassie-Baxter non-wetting state (2). In our previous research, we also demonstrated that tipple-scale surface roughness, obtained from silica aggregates functionalized with fluoroalkylsilane molecules, were superior to from stable extreme anti-wetting surface that can repel water or even highly adhesive liquid like concentrated natural latex (3). As the film was mainly composed of functionalized nanoparticles, however, its poor mechanical durability remains a major drawback for real uses.…”
Section: Introductionmentioning
confidence: 86%
“…Furthermore, surface roughness in multiple length scale has been proven as the key to achieve more stable Cassie-Baxter non-wetting state (2). In our previous research, we also demonstrated that tipple-scale surface roughness, obtained from silica aggregates functionalized with fluoroalkylsilane molecules, were superior to from stable extreme anti-wetting surface that can repel water or even highly adhesive liquid like concentrated natural latex (3). As the film was mainly composed of functionalized nanoparticles, however, its poor mechanical durability remains a major drawback for real uses.…”
Section: Introductionmentioning
confidence: 86%
“…The reduction of the coronavirus persistence on PPE surfaces can be accomplished by preventing the adhesion of the respiratory droplets onto the material surfaces [ 100 , 101 ]. To this end, metal oxides have been employed on different types of surfaces to induce biocidal effects over pathogens, as it is discussed below [ 65 , 66 , 67 , 69 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 ].…”
Section: Prevention Of Covid-19 Infection Using Biomedical Sciencementioning
confidence: 99%
“…Another proposed strategy to improve the protective equipment and increase safety among wearers is the use of tailored nanomaterials to minimize the wettability of hydrophilic droplets by using an NP-based coating [ 101 , 120 , 121 ]. In this regard, nanofibers from different nanocomposites, such as eggshell membrane and silk fibroin nanofibers, have been evaluated, by taking advantage of their hydrophobicity and biocompatibility, to reduce the wettability in biomedical applications, such as face masks [ 111 ].…”
Section: Prevention Of Covid-19 Infection Using Biomedical Sciencementioning
confidence: 99%
“…The moistureresistant liquid in this study used nanosilicate which is manufactured in-house and fluoroalkylsiloxane compound and its preparation process is as follows [16].…”
Section: Preparation Of Moisture Resistancementioning
confidence: 99%